2019
DOI: 10.3164/jcbn.19-12
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin E and cardiometabolic measures: a Mendelian randomization analysis

Abstract: Although a large body of literature reported that high intake of vitamin E played a possible role in reducing risk of cardiometabolic diseases, conflicting results were also found in some observational studies due to confounding factors. Hence, we used a Mendelian randomization study as an alternative way to examine the causality between circulating vitamin E and cardiometabolic diseases. Summary level data were extracted from consortia and three single nucleotide polymorphisms were used as instrumental variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Two previous studies using an MR approach found that a genetic predisposition to high vitamin E level was associated with increased risk of CAD (45,46).…”
Section: Illustration)mentioning
confidence: 99%
“…Two previous studies using an MR approach found that a genetic predisposition to high vitamin E level was associated with increased risk of CAD (45,46).…”
Section: Illustration)mentioning
confidence: 99%
“…Furthermore, recent meta-analyses of randomized trials found that vitamin C supplementation was not associated with TC, TG, LDL, HDL [4042], glucose, HbA1c and insulin [40,43], in line with the findings from multiple MR studies that circulating vitamin C level did not change lipids, BMI, BP [44] and glycemic traits [45]. For vitamin E, MR evidence showed that circulating vitamin E was not associated with BMI, or glucose traits [46]. Our findings of the null effects of vegetable intake are actually consistent with these recent trial and MR evidences on the antioxidants.…”
Section: Discussionmentioning
confidence: 64%
“…Wang and Xu (2019) added that higher vitamin E may increase the risk of CAD/MI and safety and efficacy of vitamin E supplementation use should be reevaluated. Fan et al (2019) found that genetically elevated vita-min E was associated with increased risk of coronary artery disease, suggested an adverse causality between circulating vitamin E and coronary artery disease. 4-Stroke: The evidence did not suggest that vitamin E supplements protect against stroke.…”
Section: Introductionmentioning
confidence: 99%